Ethnic Classification in the New Zealand Health Care System - Rata, Elizabeth (J Med Philos, 2016)
The ethnic or “racial” classification of Maori and non-Maori is a pivotal feature of New Zealand’s health system and affects government policy and professional practice within the context of Treaty of Waitangi “partnership” politics. Although intended to empower Maori, ethnic categorization can have unintended and negative consequences by ignoring the causality of material forces in social phenomena. The authors begin by showing how the use of ethnic categories in health policy is justified by the Treaty of Waitangi partnership policies. This provides the context for the argument made in the manuscript that an understanding of the social experience of ethnicity within the complex interaction of sociocultural factors such as socioeconomic location and lifestyle is more useful than using the political construct of ethnic categories in explaining the persistence of low health status for a section of the Maori population.